Inflationary Processes in Russia Amid the COVID-19 Pandemic - Dz. I. Ramazanov; E. Yu. Onopyuk (Вестник Российского экономического университета имени Г. В. Плеханова)
The article examines inflationary processes in Russia and the impact of the coronavirus recession on them. The need for this study is due to the fact that the existing factors of inflation in modern conditions "overgrown" with new causes due to changes in the world economy. Using the methods of positive and normative analysis, tabular and graphical analysis, factors that have a particular impact on inflation are considered, taking into account the events taking place in the world economy. As a result, the study showed that the exchange rate, the situation on the food market and budget financing are the factors that had the most significant impact on inflation in Russia. The conclusion is made about the significant role of the dynamics of the ruble exchange rate in the deployment of inflation, the contribution of agflation and price disparity to the consumer price index. The directions of struggle against price disparity and their use in anti-inflationary strategy are considered. The duality of the nature of public debt and inflation is revealed, a conclusion is made about the possibility of increasing public debt, and possible inflationary scenarios for the economy are given. Based on the results of the study, it is proposed to use an anti-inflationary strategy that would fully take into account inflation factors and adequate anti-inflationary policy instruments. The growth of public debt, according to the authors, will have a delayed inflationary effect; tightening of monetary policy is in conflict with the achievement of sustainable rates of economic growth. Anti-inflationary policy should be aimed at leveling external shocks while maintaining the guidelines for a stimulating monetary policy.